UJI EFEKTIVITAS ANTIOKSIDAN LOSIO EKSTRAK METANOL BUAH NAGA MERAH (Hylocereus polyrhizus Britton dan Rose) - ., Amanda Angelina Sinaga (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Hylocereus polyrhizus Britton and Rose (Red dragon fruit) has been shown tohave antioxidant activity. The fruit mainly contains vitamin C, polyphenol, flavonoid.These compound are able to prevent radicals forming which can cause aging or otherdiseases. This research was aimed to investigate antioxidant efectivity from H. polyrhizus in form of lotion. Formulation of lotion made with 5 concentration from H. polyrhizus methanol extract. There are 0,04; 0,08; 0,16; 0,32 and 0,64%. Lotion antioxidanteffectivity was analyzed with DPPH method and observed physicochemical properties areorganoleptic, dispersive power, adhesion, viscosity and pH. The research showed H.polyrhizus methanol extract had antioxidant effectivity with percent inhibition as big as19,99±0,33; 25,01±0,08; 39,14±0,04; 66,69±0,12 dan 83,37±0,05. Result data analysisshowed significantly different of the antioxidant effectivity test and the physicochemicalproperties test. Dispersive power obtained in the range of 5,55-6,9 cm, adhesion obtainedin the range 56,33-64,67 s, pH obtained in the range 7,81-7,89 and viscosity obtainedwith a value of 40 poise that showed lotion had good physicochemical and in range ofallowable. The physical stability observation of five formula with cycling test methodshowed unstability cause discolouration (oxidation). As well as the methods ofmechanical test showed unstability of lotion because saponification process. Keywords: Hylocereus polyrhizus, Antioxidant, DPPH, physicochemical test.